Cross-sectional and longitudinal association between hemoglobin concentration and hypertension: A population-based cohort study. Issue 41 (October 2016) - Kim, Na Hyun; Lee, Ju-Mi; Kim, Hyeon Chang; Lee, Joo-Young; Yeom, Hyungseon; Lee, Jung Hyun; Suh, Il
Abstract : Abstract: We investigated the cross-sectional and longitudinal associations between hemoglobin concentration and hypertension in a Korean population. Between 2006 and 2013, we examined 4899 participants with mean age of 56.6 years (range 35–88 years) from a rural community. We excluded 298 participants with a history of myocardial infarction or stroke and 264 participants with very low hemoglobin levels (men: <13.3 g/dL; women: <11.6 g/dL). Finally, we performed a cross-sectional analysis on 1629 men and 2708 women. Longitudinal associations were evaluated in 654 men and 1099 women, after excluding 2584 people with hypertension at baseline and those who did not participate in follow-up examinations. Hypertension was defined as systolic blood pressure ≥140 mm Hg, diastolic blood pressure ≥90 mm Hg, or use of antihypertensive treatment. The mean hemoglobin level was significantly higher in people with hypertension than in those without hypertension ( P = 0.002 for men, P = 0.006 for women). On cross-sectional analysis, the odds ratio (95% confidence interval) for hypertension per 1 standard deviation increase in hemoglobin concentration (1.2 g/dL) was 1.11 (1.05–1.18) before adjustment and 1.20 (1.09–1.32) after adjusting for age, sex, body mass index, kidney markers, lifestyle factors, and comorbidities. On longitudinal analysis, the relative risk (95% confidence interval) for incident hypertension per 1 standard deviation increase in hemoglobin concentration was 1.09 (0.96–1.23) before adjustment and 0.91 (0.78–1.08) after adjusting for age, sex, body mass index, lifestyle factors, baseline blood pressure, baseline comorbidities, and baseline kidney markers. This study suggests that hemoglobin per se does not cause hypertension development. Abstract : Supplemental Digital Content is available in the text